2017
DOI: 10.1080/19475705.2017.1327464
|View full text |Cite
|
Sign up to set email alerts
|

Real-time prediction of water level change using adaptive neuro-fuzzy inference system

Abstract: Accurate water levels modelling and prediction is essential for maritime applications. Water prediction is traditionally developed using the leastsquares-based harmonic analysis method based on water level change (WLC) measurements. If long water level measurements are not obtained from the tide gauge, accurate water levels prediction cannot be estimated. To overcome the above limitations, the wavelet neural network (WNN) has recently been developed for the WLC prediction from short water level measurements. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In other words, ANFIS is defined as a system that uses fuzzy rules and the associated fuzzy inference method for learning and rule optimization purposes [46]. In this study, we apply the combined learning rule, which uses conventional back-propagation and least square methods to estimate the parameters of the model accurately [47]. e model is made up of five layers.…”
Section: Adaptive Neurofuzzy Interference System (Anfis)mentioning
confidence: 99%
“…In other words, ANFIS is defined as a system that uses fuzzy rules and the associated fuzzy inference method for learning and rule optimization purposes [46]. In this study, we apply the combined learning rule, which uses conventional back-propagation and least square methods to estimate the parameters of the model accurately [47]. e model is made up of five layers.…”
Section: Adaptive Neurofuzzy Interference System (Anfis)mentioning
confidence: 99%
“…Additionally, [27] employed the ANFIS model to predict Water Level Change (WLC) models of a month of hourly WLC for Yarmouth, Sain-John, and Charlottetown stations in Canadian waters, and then compared it with the results obtained using the wavelet neural network (WNN) model. The results obtained showed that the ANFIS model is superior.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Soft computing techniques have successfully used in the last three decades to solve different complex hydrological problems (Daliakopoulos et al, 2005;Ehteram et al, 2021;Hadi et al, 2019;Kaloop et al, 2017;Malik et al, 2020b;Parsaie et al, 2015;Sammen et al, 2017;Singh et al, 2018;Tikhamarine et al, 2020c;Yaseen et al, 2020b;Young et al, 2015). For water level prediction, several techniques have been used such as Artificial Neural Networks (ANN) (Alvisi et al, 2006), Autoregressive Integrated Moving Average (ARIMA) (Reza et al, 2018;Sihag et al, 2020;Xu et al, 2019), and Support Vector Machine (SVM) (Khan & Coulibaly, 2006;Liong & Sivapragasam, 2002).…”
Section: Introductionmentioning
confidence: 99%